Right of women to obtain divorce under shari‘ah and Islamic Family Law of Malaysia: with special reference to Ta’liq and Khulu’ - Abdul Hak, Nora; Che Soh @ Yusoff, Roslina; Ibrahim, Norliah; Niringjuerae, Manawee (INSI Publications, 2012)
In Islam, marriage is expected to last until one of the spouses dies. However, if the spouses cannot live together in peace and harmony any more in the marital relationship, then its continuance is no longer considered desirable. Divorce is permitted as a matter of necessity for the avoidance of greater evil, which may result from the continuance of themarriage. The failure of marriage can be due to many reasons such as certain defects or faults in one or both of the spouses which give the right to apply for khulu’ or ta’liqto the wife and talaq to the husband. When the wife’s conduct is undesirable such as nushuz(marital discord) to her husband, the husband is permitted to divorce her. When the husband becomes a transgressor, for example, the husband is incapable of maintaining the wife or he ill-treats the wife,Islam also grants women the right to dissolve the marriage. Men and women have similar rights and obligations to one another. For that reason, Islam provides some grounds for women to obtain divorce. This article focuses on two grounds of divorce that are available in Islam i.e., khulu’ and ta’liq. It also discussescases decided at the Shari‘ah court and the procedure provided under the Islamic family law for women to exercise these rights of divorcei.e., ta’liq and khulu’in Malaysia.